ANALISIS PENERAPAN PROGRAM KESELAMATAN KERJA DALAM USAHA MENINGKATKAN PRODUKTIVITAS KERJA DENGAN PENDEKATAN FAULT TREE ANALYSIS DAN HAZARD AND OPERABILITY STUDY - Yetti Meuthia Hasibuan; Rini Halila Nasution; Uun Novalia Harahap; Rafika Apriani Pratiwi; Wan Krisman Hia (Jurnal Simetri Rekayasa, 2020)
PT. Sumatra Hakarindo in its operation is not free from problems encountered such as work accidents, occupational diseases and the negative impact of the industry on the surrounding environment, so the level of human work safety as a factor of production is needed so that optimal productivity can be achieved. The application of work safety programs for workers is an important supporting effort in production activities. The work safety program system consists of several program elements and their supporters. In this study the measurement of the results of work safety efforts and the safe T value, the frequency level to express the number of accidents that occur every 1,000,000 hours worked from the employee's "work hours" home. The safe T value is a measurement that aims to compare the results of the accident reduction rate achieved for that work. From the implementation of the Occupational Health program at PT. Sumatra Hakarindo can be said to have been implemented quite well. Accidents that occurred in 2018 -2020 were 15,13,11 accidents. With a frequency rate from 2018-2020 it is 64.6; 49.9; 36,1. The severity level that occurred in 2016-2018 was 458.9; 284.2; 233,2. With a safe T value in 2018 it is known - 950.2 in 2019 it is - 1098.2. The decrease in accident rates and the severity of accidents from year to year will increase labor productivity.